High efficiency X-band relativistic backward wave oscillator with non-uniform slow wave structures - 吴洋 许州 李正红 马乔生 唐传祥 (Chinese physics C, 2012)
Backward wave oscillators （BWOs） driven by intense relativistic electron beams are very efficient means of producing high-power microwaves. However, the efficiency of conventional BWO is lower than 30%. An X-band oversized BWO with non-uniform slow wave structure is designed to improve RF output characteristics. In particle-in-cell simulation, a high power microwave with a power of 8.0 GW and efficiency of 40% is obtained, compared with that of 30% obtained in a conventional relativistic BWO.